Selênio na castanha-do-brasil (Bertholletia excelsa) e em solos da região Amazônica Brasileira - Silva Júnior, Ediu Carlos da (2016)
Brazil nuts (Bertholletia excelsa) is characterized as one of the most important non-timber products from the Amazon region, since it is a food greatly appreciated by local communities and used for exportation. The Brazilian nuts are recognized worldwide as the richest food source of selenium (Se), increasing with the development of research that increasingly is proving its beneficial effects on human health. Selenium is a trace element that presents essential or toxic properties depending on the concentration range in ingested food. Worldwide, there are situations of both deficiency and toxicity of Se in soils, reflecting the element content in the foods we eat. In regions where the soil Se content is low, alternatives to improve nutrition of the population are required, for example via agronomic biofortification, or even by using natural sources for Se improvement in food, as in the case of Brazil nuts. This study aimed to better understand and characterize the Se levels in Brazil nuts. Samples were collected in their natural environment of production and crops established in different regions of the Amazon basin, yet, aiming perform correlation between the levels of Se present in nuts and soil where these plants are located. Fruit samples were collected in the states of Acre (15 plants), Mato Grosso (13 plants), Roraima (15 plants), Amapá (15 plants) and Amazon (17 plants) and soil samples at 0-20 cm, 20-40 cm and 40-60 cm layers, in order to analyze the total Se content in both plant material and soil. The results showed that the total concentration in soil ranged from < 65.76 to 737.76 µg kg-1 (average of 278.28 µg kg-1 ), and 75% of the soil samples were lower than 361.08 µg kg-1 . The total Se content obtained in Brazil nut samples allowed us to divide the samples into three groups: 1) Plants that have low concentrations (Acre and Mato Grosso) with average of 7.54 mg kg-1 and 6.79 mg kg-1 respectively; 2) plants with intermediate concentrations (Roraima) with an average content of 18.86 mg kg-1 and 3) plants with high concentrations (Amapá and Amazonas) with average levels of 59.35 mg kg-1 and 86.33 mg kg-1 respectively. The regression models and principal component analysis (PCA) showed that the total soil Se content is not the main factor determining the Se content in Brazil nuts and, therefore little predictive of these values. On the other hand, the pH has demonstrated its importance association with the Se availability in the soil for the plants, especially in the 0-20 cm layer.